Models and applications for measuring the impact of health research: update of a systematic review for the Health Technology Assessment programme. - Raftery, James (Health Technol Assess, 2016)
BACKGROUND: This report reviews approaches and tools for measuring the impact of research programmes, building on, and extending, a 2007 review. OBJECTIVES: (1) To identify the range of theoretical models and empirical approaches for measuring the impact of health research programmes; (2) to develop a taxonomy of models and approaches; (3) to summarise the evidence on the application and use of these models; and (4) to evaluate the different options for the Health Technology Assessment (HTA) programme. DATA SOURCES: We searched databases including Ovid MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature and The Cochrane Library from January 2005 to August 2014. REVIEW METHODS: This narrative systematic literature review comprised an update, extension and analysis/discussion. We systematically searched eight databases, supplemented by personal knowledge, in August 2014 through to March 2015. RESULTS: The literature on impact assessment has much expanded. The Payback Framework, with adaptations, remains the most widely used approach. It draws on different philosophical traditions, enhancing an underlying logic model with an interpretative case study element and attention to context. Besides the logic model, other ideal type approaches included constructionist, realist, critical and performative. Most models in practice drew pragmatically on elements of several ideal types. Monetisation of impact, an increasingly popular approach, shows a high return from research but relies heavily on assumptions about the extent to which health gains depend on research. Despite usually requiring systematic reviews before funding trials, the HTA programme does not routinely examine the impact of those trials on subsequent systematic reviews. The York/Patient-Centered Outcomes Research Institute and the Grading of Recommendations Assessment, Development and Evaluation toolkits provide ways of assessing such impact, but need to be evaluated. The literature, as reviewed here, provides very few instances of a randomised trial playing a major role in stopping the use of a new technology. The few trials funded by the HTA programme that may have played such a role were outliers. DISCUSSION: The findings of this review support the continued use of the Payback Framework by the HTA programme. Changes in the structure of the NHS, the development of NHS England and changes in the National Institute for Health and Care Excellence's remit pose new challenges for identifying and meeting current and future research needs. Future assessments of the impact of the HTA programme will have to take account of wider changes, especially as the Research Excellence Framework (REF), which assesses the quality of universities' research, seems likely to continue to rely on case studies to measure impact. The HTA programme should consider how the format and selection of case studies might be improved to aid more systematic assessment. The selection of case studies, such as in the REF, but also more generally, tends to be biased towards high-impact rather than low-impact stories. Experience for other industries indicate that much can be learnt from the latter. The adoption of researchfish(®) (researchfish Ltd, Cambridge, UK) by most major UK research funders has implications for future assessments of impact. Although the routine capture of indexed research publications has merit, the degree to which researchfish will succeed in collecting other, non-indexed outputs and activities remains to be established. LIMITATIONS: There were limitations in how far we could address challenges that faced us as we extended the focus beyond that of the 2007 review, and well beyond a narrow focus just on the HTA programme. CONCLUSIONS: Research funders can benefit from continuing to monitor and evaluate the impacts of the studies they fund. They should also review the contribution of case studies and expand work on linking trials to meta-analyses and to guidelines. FUNDING: The National Institute for Health Research HTA programme.